Feminism Perspective in the Novel Cinta di dalam Gelas by Andrea Hirata - Rabiatul Adawiyah Siregar (Proceedings of AICS - Social Sciences, 2017)
Abstract This research aims to find out socio-cultural background of Andrea Hirata and gender perspective in his novel Cinta di dalam Gelas(Hirata, 2011) based on a review of feminism literature. Andrea Hirata is an Indonesian author best known novel from Belitung. Feminism is aimed to the balance or gender interaction. As Ratna (2012, p. 184) says that feminism is females move in refusing everything imagined, subordinated, and degraded by dominant culture in politics, economics, and social life in general as well. This is a qualitative research with descriptive analysis. The object of this research is the structure and the existence of gender perspective portrayed by the protagonist, Maryamah. Data collection procedure is done by library research, refer to, and record with the novel itself as the main data. Data analysis technique is done by heuristics and hermeneutics techniques. Results show that the social background of the writer of the novel actually comes from Belitong that inspired the novel. Gender perspective in novel Cinta di dalam Gelasincludes gender equalities and inequalities in the novel happened in many aspect of life. Those are equality in education, equality in politics view and organization, equality in social culture. Meanwhile, gender inequalities include female subordination, female stereotype, violence against women, and women's workload. Keywords:gender perspective, gender equality, novel, feminism.